Changes in Student Perceptions of Ethics of Learning Analytics due to the Pandemic - Nevaranta Matias; Lempinen Katja; Kaila Erkki (Germany, 2022)
The pandemic has affected all areas of life with education being no different. Distance learning has become the new normal in all levels of education. Learning analytics as a tool best utilized by the abundance of data should now be more lucrative and needed than ever. Prior to the change, we surveyed the students of two Finnish higher education institutes, Helsinki university and Satakunta university of applied sciences, about their opinions, attitudes and expectations of learning analytics and ethics associated with it. This study is a follow-up surveying only the students of university of applied sciences and aims to find changes that might have been brought forth by the sudden and drastic switch to distance learning only. In addition, this was a chance to gather information on the students’ experiences on distance learning, and how they feel about the so called new normal. The results seem to indicate that while students' expectations towards learning analytics haven't changed, their attitudes to security of their data and ethical conduction of analytics have become significantly stricter. We also found out that students have diverse feelings about distance learning in general, indicating changes required to post-pandemic education.
Proceedings of the Conference on Technology Ethics Turku, Finland, October, 20-22, 2021